SKRINING DAN ANALISIS KLT-BIOAUTOGRAFI SENYAWA ANTIMIKROBA BEBERAPA EKSTRAK SPONS ASAL PERAIRAN LAUT PULAU BARRANG LOMPO, SULAWESI SELATAN - Risfah Yulianty; Herlina Rante; Gemini Alam; Akbar Tahir (Majalah Obat Tradisional, 2011)
Sponges is one of the invertebrate Porifera phyla that produce active compounds with various structures and one of the biological activity as antimicrobial. The purpose of this research was to find out the sponge extracts that can inhibit microbial growth and potential of antimicrobial active compounds from sponge at Barrang Lompo Island. The microbes used were Escherichia coli, Salmonella typhii, Staphylococcus aureus, and Candida albicans. The sponge extracts were obtained by maceration 14 sponge samples with methanol, followed by partition using chloroform and methanol, then TLC-bioautography toward the active extract. The results showed that methanol extracts of sponge with code BRLP-009 and 010 have the most potential effect as antimicrobial agent.